The Effectiveness of a Training Program for Pre-Service Social Studies Teachers Based on International Teacher Preparation Requirements in Developing Differentiated Teaching Skills and Cultural Diversity Values - Al-Zeinati, Malak Jamal; Al-Tawalbah, Hadi Mohammed (Journal of Posthumanism, 2025)
Objectives: The current study aimed to examine the effectiveness of a training program for pre-service social studies teachers based on international teacher preparation requirements in developing their differentiated teaching skills and cultural diversity values. Methods: a quasi-experimental approach was employed. Two research instruments were developed: a differentiated teaching skills scale and a cultural diversity values test, both of which were validated for reliability and validity. The study sample consisted of 30 pre-service social studies teachers from the Faculty of Educational Sciences at Yarmouk University during the 2024-2025 academic year. Results: The findings revealed statistically significant differences in the differentiated teaching skills scale between the pre-test and post-test, favoring the post-test results. Similarly, statistically significant differences were found in the cultural diversity values test between the pre-test and post-test, also in favor of the post-test. These results indicate the effectiveness of the training program in enhancing differentiated teaching skills and cultural diversity values among pre-service social studies teachers.Conclusions: The findings revealed statistically significant differences in the differentiated teaching skills scale between the pre-test and post-test, favoring the post-test results. Similarly, statistically significant differences were found in the cultural diversity values test between the pre-test and post-test, also in favor of the post-test. These results indicate the effectiveness of the training program in enhancing differentiated teaching skills and cultural diversity values among pre-service social studies teachers.